Impact of spinal fusion on severity health status in scoliotic adolescents with polyhandicap. - Hugo Bessaguet; Marie-Christine Rousseau; Vincent Gautheron; Etienne Ojardias; Bruno Dohin (PLoS ONE, 2024)
Background Scoliosis constitutes a prevalent comorbidity in adolescents with polyhandicap and frequently leads to other severe impairments, impacting abilities and requiring complex caregiving strategies. Therefore, spinal fusion surgeries are commonly performed to alleviate pain and provide more comfort. However, spine stabilization has not previously been proven to improve the severity health status of adolescents with polyhandicap according to specific clinical scales. Objective This study describes and compares the severity health status of adolescents with polyhandicap before and after they underwent spinal fusion. Methods A monocentric retrospective observational study was conducted in the university hospital centre of Saint-Etienne, France. We included between 2009 to 2020, 30 scoliotic adolescents with polyhandicap who underwent spinal fusion performed with the same surgical technique and the same surgeon. The main outcome was the variation in the Polyhandicap Severity Scale (PSS) score after surgery. Secondary outcomes were variations in PSS subscores, quality of life scores, fronto-sagittal X-ray parameters, and measures of surgical complication rates and lengths of stay. Results Among 30 adolescents, 27 PSS analyses were performed. We found a significant improvement between pre- and postoperative PSS scores, mainly for pain and respiratory, digestive, and skin disabilities. These improvements were accompanied by significant reductions in pelvic obliquity, in frontal and sagittal curves. The mean hospital length of stay was 45 days. During postoperative period, patients received a personalized postoperative rehabilitation procedure with spasticity and pain treatments, physiotherapy, and verticalization (wheelchair sitting and positioning devices such as contoured seat intended to increase postural stability). The mortality rate was estimated at 7%. At least 1 complication per patient occurred. Conclusions We show that spinal fusion surgeries confer a significant improvement in the severity health status in scoliotic adolescents with polyhandicap.